Commentary on prescribing ethics and conflict of interest - Amna Rehana Siddiqui; Mishal Sameer Khan (Journal of the Pakistan Medical Association, 2024)
The medical profession is inherently built on the pillars of trust, integrity and ethical conduct. Patients entrust their health, and often their lives, to medical practitioners, expecting that the care they receive is solely guided by the patient’s best interest. However, with the complexities of modern healthcare, these ethical standards are increasingly difficult to maintain. Conflict of interest in healthcare arises when the professional judgment of a healthcare provider is compromised such that they are at risk of not acting in the best interest of the patient because of the potential for personal gain.1-3 The theme of this supplement issue being conflict of interest (COI) affecting medical practice is a challenge particularly in the settings where regulatory systems are underresourced. Conflict of interest in health care provision not only occurs in physicians, but also among pharmacists and laboratory workforce. The healthcare provider-patient relationship is one of trust and confidence that the healthcare provider will act to maximize better health outcomes for the patient; therefore, the challenge of conflict of interest and unethical medical practices need to be addressed improving the quality of care and maintain trust in health systems.2-3 Continued...